Mass-separation of impurities in the ion beam systems with reversed magnetic beam focusing - Girka, O.I.; Bizyukov, I.A.; Bizyukov, A.A.; Sereda, K.N.; Herashchenko, S.S. (Вопросы атомной науки и техники, 2012)
This paper describes the intrinsic capability of ion systems with reversed magnetic beam focusing for impurities mass-separation. Numerical calculation of the ion trajectory deviation with taking into account the experimental ion energy distribution function for hydrogen-oxygen gas mixture was carried out. It is demonstrated that O⁺ impurities which are present in the beam are separated and form the circle with a diameter of ≈6 mm. Therefore, the central part of the spot is free of impurities due to magnetic separation. As a result, the source generates steady-state hydrogen ion beam, which irradiates the surface with high heat and particle fluxes, which approach the upper limit for the flux range expected in a fusion reactor. Исследованы особенности масс-сепарации примесей в ионно-пучковых системах с реверсивной магнитной фокусировкой пучка. Численно рассчитаны отклонения траекторий ионов с учетом экспериментально измеренной функции распределения энергии ионов для водородно-кислородной газовой смеси. Показано, что примеси О⁺ в пучке сепарируются и формируют кольцо диаметром ≈ 6 мм. Таким образом, центральная часть пучка чиста от примесей вследствие магнитной сепарации. В результате источник генерирует стационарные мощные потоки тепла и ионов водорода, которые близки по своим параметрам к потокам, ожидаемым на материалы стенки термоядерного реактора. Досліджено можливість мас-сепарації домішок в іонно-пучкових системах з реверсивним магнітним фокусуванням пучка. Чисельно розраховано відхилення траєкторій іонів з урахуванням експериментально зміненої функції розподілу енергії іонів для воднево-кисневої газової суміші. Показано, що домішки О⁺ в пучку сепаруються та формують кільце діаметром ≈ 6 мм. Таким чином, центральна частина пучка є чистою від домішок унаслідок магнітної сепарації. В результаті джерело генерує стаціонарні потужні потоки тепла і іонів водню, які близькі за своїми параметрами до потоків, очікуваних на матеріали стінки термоядерного реактора.